2015
DOI: 10.1074/jbc.m114.624411
|View full text |Cite
|
Sign up to set email alerts
|

Oncoprotein YAP Regulates the Spindle Checkpoint Activation in a Mitotic Phosphorylation-dependent Manner through Up-regulation of BubR1

Abstract: Background: Oncoprotein YAP regulates cell proliferation and tumorigenesis, and a cellular function of YAP in mitosis is largely unknown. Results: YAP and its mitotic phosphorylation regulate the spindle checkpoint through up-regulation of BubR1. Conclusion:The findings reveal a novel link between YAP and the spindle checkpoint. Significance: Our studies indicate a potential mechanism underlying the oncogenic function of YAP through dysregulation of the spindle checkpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Interestingly, we also found that several Hippo core members (Lats1, Lats2, and Mst2) (Fig. 1) or their upstream regulator (KIBRA) (30,31) or downstream effectors (YAP and TAZ) (12,13,15) are phosphorylated during mitosis. Importantly, mitotic phosphorylation is critical for their oncogenic or tumor suppressive functions (12,13,15).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Interestingly, we also found that several Hippo core members (Lats1, Lats2, and Mst2) (Fig. 1) or their upstream regulator (KIBRA) (30,31) or downstream effectors (YAP and TAZ) (12,13,15) are phosphorylated during mitosis. Importantly, mitotic phosphorylation is critical for their oncogenic or tumor suppressive functions (12,13,15).…”
Section: Discussionmentioning
confidence: 84%
“…For example, loss of core tumor suppressors in the Hippo pathway (including Lats2, Mst1/2, Mob1, and WW45) leads to severe defects in multiple mitotic processes (39 -41). Accordingly, we recently reported that overexpression of active YAP (12,13) or TAZ (15) is sufficient to trigger mitotic defects, including centrosome amplification, spindle disorganization, chromosome misalignment, and subsequent aneuploidy. Interestingly, we also found that several Hippo core members (Lats1, Lats2, and Mst2) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…YAP and TAZ are phosphorylated at multiple sites by CDK1 during the G2/M phase of the cell cycle (Yang et al 2013(Yang et al , 2015bZhao et al 2014;Dent et al 2015;Zhao and Yang 2015). However, the physiological outcomes of these phosphorylation events are rather perplexing, as their effects on cell growth and migration are not entirely consistent among reports from different groups.…”
Section: Cell Cyclementioning
confidence: 99%